2014
DOI: 10.1161/circulationaha.113.005186
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Comparison of Xience V and Multi-Link Vision Coronary Stents in the Same Multivessel Patient With Chronic Kidney Disease (RENAL-DES) Study

Abstract: Background-Percutaneous coronary interventions in patients with chronic kidney disease have shown suboptimal results. Drug-eluting stents (DES) might reduce the rate of target vessel revascularization in comparison with baremetal stents (BMS) in patients with chronic kidney disease. However, given the multiple concomitant individual variables present in such patients, the comparison of neointimal growth after percutaneous coronary intervention is complex and difficult to assess. Methods and Results-Randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…14 Studies with intraindividual design are a valuable adding to investigations of device efficacy. [6][7][8] To the best of our knowledge, studies exploring BVS and DES in the same patient receiving multilesion PCI have not been performed. Against this background, this report investigates the intraindividual performance of BVS and DES in patients receiving multilesion PCI and subsequent angiographic surveillance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14 Studies with intraindividual design are a valuable adding to investigations of device efficacy. [6][7][8] To the best of our knowledge, studies exploring BVS and DES in the same patient receiving multilesion PCI have not been performed. Against this background, this report investigates the intraindividual performance of BVS and DES in patients receiving multilesion PCI and subsequent angiographic surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…5 Studies comparing intrapatient differences in stent outcomes remain an important tool for assessing comparative device efficacy: indeed, by excluding the baseline variability between patients (not completely eliminated even with a random allocation), the intraindividual design offers the advantage of a net-effect analysis of treatments. 6 Previous intraindividual studies of DES efficacy have generally shown similar outcomes to randomized trials comparing stents. [6][7][8] However, angiographic and clinical outcomes of BVS and DES in the same individual receiving multilesion percutaneous coronary intervention (PCI) have yet to be investigated.…”
Section: See Editorial By Ormiston and Webstermentioning
confidence: 91%
See 1 more Smart Citation
“…Therefore, no conclusions were made in terms of ESRD. RENAL-DES was the first randomized trial showing effectiveness in terms of clinical restenosis of second-generation EES in comparison with bare metal stent in patients with chronic kidney disease (CKD), and the efficacy of EES in preventing restenosis was independent of the severity of CKD, including severe CKD and kidney failure [8]. However, it remains unclear whether there are differences in clinical outcomes between EES and PES in patients with ESRD, especially those on dialysis.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Preferably, the influence of lesionrelated factors would be minimized by randomly allocating individual lesions to one or other treatment.…”
mentioning
confidence: 99%